2020
DOI: 10.1051/e3sconf/202015101015
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Testosterone Concentrations with Scrotal Circumference, and Semen Characteristics in Aceh Bulls

Abstract: This study was conducted to examine testosterone concentrations its relationship with the scrotal circumference and physical characteristics of semen in aceh bulls. Semen samples were collected weekly from jugular vein of three aceh bulls aged 4-5 years old for 10 weeks. Testosterone concentration was measured by enzyme-linked immunosorbent assay (ELISA) method. Semens were collected by using artificial vagina and evaluated for physical characteristics namely ejaculatory volume, pH, and sperm motility, concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 12 publications
1
9
0
1
Order By: Relevance
“…As shown in Figure -1, there was a correlation between decreased testosterone concentrations and an increased level of abnormal sperm in the group aged 8-10 years (10.20%). Our findings are in line with those of Dasrul et al [6], who reported a relationship between testosterone concentration and semen quality (sperm motility and sperm abnormalities) in Aceh bulls and also crossbred cattle of Holstein Friesian×Tharparkar [20]. Several studies also have shown that low semen quality is associated with a deficiency in testosterone concentrations [21].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As shown in Figure -1, there was a correlation between decreased testosterone concentrations and an increased level of abnormal sperm in the group aged 8-10 years (10.20%). Our findings are in line with those of Dasrul et al [6], who reported a relationship between testosterone concentration and semen quality (sperm motility and sperm abnormalities) in Aceh bulls and also crossbred cattle of Holstein Friesian×Tharparkar [20]. Several studies also have shown that low semen quality is associated with a deficiency in testosterone concentrations [21].…”
Section: Discussionsupporting
confidence: 93%
“…The reaction was stopped by adding 100 µL of stop solution to each microplate well. We then determined the absorbance at 450 nm using an ELISA reader [6].…”
Section: Measurement Of Testosterone and Adiponectin Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction stopped by adding 100 µL of stop solution to each well. The absorbance was read using an ELISA reader at 450 nm (Dasrul et al 2020;Hafizuddin et al 2020).…”
Section: Testosterone Concentration Assessmentmentioning
confidence: 99%
“…Notre valeur observée était comparable à celles rapportées pour des taureaux de taille semblable : 22,7 cm a été observée chez des taureaux de race Ndama d'un poids moyen de 151 kg (Akouango et al, 2010). Des valeurs de 29,75 ± 3,18 cm, 27,5 ± 2,12 cm et 28,02 ± 2,23 cm ont été mentionnées respectivement pour des taureaux Bos indicus de race Borgou, Azawak (Akpo et al, 2018) et Aceh (Dasrul et al, 2020). Une valeur moyenne de 25,9 cm a été observée chez des taureaux de race Brune de l'Atlas âgés de 12-18 mois par Rahmani et al (2019).…”
Section: Déclaration Des Contributions Des Auteursunclassified